Do Bureaucrats Contribute to the Resource Curse? Evidence from a Survey Experiment in New Oil States. Issue 4 (3rd April 2022) - Sigman, Rachel; Harris, Adam S.; Meyer-Sahling, Jan-Hinrik; Mikkelsen, Kim Sass; Schuster, Christian
Abstract: The resource curse literature argues that oil production reshapes the fiscal contract between citizens and the state: politicians become less responsive to citizen taxpayers and more likely to use public revenues for their own benefit. This paper examines whether and how bureaucrats influence this breakdown of the fiscal contract. Analysing results of a survey experiment conducted with government employees in Ghana and Uganda, we find that, when primed to think about oil revenue, bureaucrats do not generally express attitudes indicating that they contribute to the resource curse. Although oil revenue does lead some Ghanaian bureaucrats to become less interested in responding to taxpayers, this finding does not operate as predicted, i.e. by bureaucrats expressing greater partiality towards the ruling elite. Instead, we attribute this outcome to 'disgruntled employees' – political outsiders with low salaries – who, unlikely to benefit from oil revenue, become disaffected from citizen service. The results shed new light on processes through which resource extraction changes state institutions.